Evaluation of the Betulinic Acid–Cisplatin conjugate APC and its precursor DE9B for the treatment of human malignant glioma. (1st December 2019) - Bache, Matthias; Hein, Anja; Petrenko, Marina; Güttler, Antje; Keßler, Jacqueline; Wichmann, Henri; Kappler, Matthias; Emmerich, Daniel; Paschke, Reinhard; Vordermark, Dirk
Abstract: Despite the existence of multimodal therapy concepts, glioblastoma remains a tumor type with one of the worst prognoses. In particular, the poor prognosis is due to the lack of therapeutic efficacy of chemical agents and irradiation in hypoxic tumor areas. New therapeutic strategies could improve the treatment of glioblastoma. In this study, we investigated the therapeutic efficacy of a conjugate of cisplatin (DDP ), a widely used chemotherapeutic agent, and betulinic acid (BA ), a natural product from plane tree bark, in glioblastoma cells under different oxygen conditions. We investigated the effects of the BA-DDP conjugate κ N ′, N ''-{3-acetyloxy-BA-28-[2-(2-aminoethyl)aminoethyl]amide} dichlorido platinum(II) (APC ) and its precursor 3-acetyloxy-BA-28-[2-(2-aminoethyl)aminoethyl]amide (DE9B ) on cytotoxicity, cell growth, apoptosis, migration and radiosensitivity compared to BA or DDP alone under different oxygen conditions. Based on the EC50 values, the precursor DE9B exhibited the strongest cytotoxic effects of the analyzed chemotherapeutic agents. The BA-DDP conjugate APC achieved a moderate cytotoxic effect in glioma cells. Both of the newly developed agents induced cell growth delay, apoptosis and inhibition of migration. Furthermore, additive effects could be achieved in combination with irradiation. In contrast to those of BA and DDP, the cell biological effects of APC and DE9B were not influenced by the oxygen concentration. In this study, the linking of BA and DDP did not produce a compound with additive therapeutic effects on glioblastoma cell lines in vitro . Nevertheless, the results of this study suggest that the precursor DE9B is an effective BA derivative for the treatment of glioblastoma in vitro . Highlights: DE9B, an alkylamide of BA, showed antitumor therapeutic efficacy in glioblastoma. DE9B is suitable for combination with irradiation. DE9B has no hypoxia-specific effect. Linking of BA and DDP did not produce a compound with additive therapeutic effect.